Subject specific pedagogy based on discovery learning and volcanic eruption disasters: Does it affect students’ concept mastery? - Tyas, Rizki Arumning; Pujianto, Pujianto; Suyanta, Suyanta (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2020)
This study aimed to determine the effect of science Subject Specific Pedagogy Based on Discovery Learning and Volcanic Eruption Disasters on students' concept mastery. This research was a quasi-experiment study with two sample groups, the experimental and the control classes of SMP N 2 Cangkringan. The instrument for collecting the concept mastery data were 35 items. The data were analyzed using descriptive and inferential analysis. The descriptive analysis employed the gain score's categorization, while the inferential analysis employed the independent sample t-test and effect size test using Partial Etta Square. The results showed an effect of the science subject-specific pedagogy based on discovery learning and volcanic eruption disaster on student’s concept mastery with a gain score of 0.79 (high) in the experimental class. In contrast, the control class obtained 0.07 (low). The independent sample t-test showed that the significance value obtained was 0,000. The effect size value seen from the Partial Etta Square statistics was 0.924, which showed that the science Subject Specific Pedagogy Based on Discovery Learning and Volcanic Eruption Disasters on the concept mastery is very strong. Thus, it can be concluded that the use of science Subject Specific Pedagogy Based on Discovery Learning and Volcanic Eruption Disasters can increase the student's science concept mastery. Further integration and development can be done for other types of disasters because it is one of the nature symptoms that also an object of natural science. Thus, natural science learning will be more meaningful because it is attached to the phenomena in the students' daily lives.